Micropolitics in collective learning spaces for adaptive decision maki ng - Tschakert, Petra; Das, Partha Jyoti; Shrestha Pradhan, Neera; Machado, Mario; Lamadrid, Armando; Buragohain, Mandira; Hazarika, Masfique Alam (Global Environmental Change, 2016)
Recent advances on power, politics, and pathways in climate change ada ptation aim to re-frame decision-making processes from development-as- usual to openings for transformational adaptation. This paper offers e mpirical insights regarding decision-making politics in the context of collective learning through participatory scenario building and flexi ble flood management and planning in the Eastern Brahmaputra Basin of Assam, India. By foregrounding intergroup and intragroup power dynamic s in such collective learning spaces and how they intersect with exist ing micropolitics of adaptation on the ground, we examine opportunitie s for and limitations to challenging entrenched authority and subjecti vities. Our results suggest that emancipatory agency can indeed emerge but is likely to be fluid and multifaceted. Community actors who are best positioned to resist higher-level domination may well be imbricat ed in oppression at home. While participatory co-learning as embraced here might open some spaces for transformation, others close down or r emain shut.
Keywords: Co-learning; Flood management; Participatory scenarios; Politics of adaptation; Power